1997
DOI: 10.1021/jm960733n
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic Activity of Novel Water-Soluble 2β-Morpholinyl Steroids and Their Modulatory Effects at GABAAReceptors

Abstract: (3 alpha,5 alpha)-3-Hydroxypregnan-20-ones and (3 alpha,5 alpha)-3-hydroxypregnane-11,20-diones bearing a 2 beta-morpholinyl substituent were synthesized, and the utility of these steroids as anesthetic agents was evaluated through determination of their potency and duration of hypnotic activity in mice after intravenous administration. Alkylation of the morpholinyl substituent or chlorination at C-21 afforded the novel amino steroids (2 beta,3 alpha,5 alpha)-3-hydroxy-2-(2,2-dimethyl-4-morpholinyl)-pregnane-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The estimated in vivo K PD for alphaxalone of 432 Ϯ 26 ng ⅐ ml Ϫ1 is in the range of values reported for the (indirect) inhibition of 35 S-t-butylbicyclophosphorothionate binding by alphaxalone, for which the IC 50 varied between 110 and 180 ng ⅐ ml Ϫ1 (Hill Venning et al, 1996;Anderson et al, 1997) and values reported for in vitro functional studies with recombinant receptors, for which the EC 50 was ϳ730 ng ⅐ ml Ϫ1 (Hill Venning et al, 1996). Using this mechanism-based PK/PD approach for the determination of the in vivo K PD will allow comparison between biphasic EEG effects of other compounds, but also between these biphasic EEG effects and other pharmacodynamic endpoints in vivo and in vitro studies.…”
supporting
confidence: 51%
“…The estimated in vivo K PD for alphaxalone of 432 Ϯ 26 ng ⅐ ml Ϫ1 is in the range of values reported for the (indirect) inhibition of 35 S-t-butylbicyclophosphorothionate binding by alphaxalone, for which the IC 50 varied between 110 and 180 ng ⅐ ml Ϫ1 (Hill Venning et al, 1996;Anderson et al, 1997) and values reported for in vitro functional studies with recombinant receptors, for which the EC 50 was ϳ730 ng ⅐ ml Ϫ1 (Hill Venning et al, 1996). Using this mechanism-based PK/PD approach for the determination of the in vivo K PD will allow comparison between biphasic EEG effects of other compounds, but also between these biphasic EEG effects and other pharmacodynamic endpoints in vivo and in vitro studies.…”
supporting
confidence: 51%
“…Neuroactive steroids have long been known to produce anesthesia (Seyle, 1942), but the clinical development of neuroactive steroid anesthetics has been hampered by side effects that are in part related to the pharmaceutical formulation required for the intravenous administration (Anderson et al, 1997;Sear, 1998). At present, there is a renewed interest in the efficacy of neuroactive steroids for the management of epilepsy, anxiety, insomnia, migraine, drug dependence, depression, stress, and premenstrual syndrome (Gasior et al, 1997;Rupprecht and Holsboer, 1999).…”
mentioning
confidence: 99%
“…5,6 Trans diaxial opening of this epoxide accounted for the regioselectivity of the reaction, giving rise to the 3α-OH moiety, a requisite for GABA A receptor activity. The intramolecular version of this process involving a nucleophile attached to C-19, besides being energetically more favorable, would result in the formation of a bridge between positions 2β and 19.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of the olefin mixture with m-chloroperbenzoic acid (MCPBA) in the presence of sodium carbonate gave the expected α-epoxides 7b and 8b (from 13 and 14, respectively). 6,14 The 1 H NMR spectrum of the crude reaction product showed the characteristic resonances for epoxides at 3.1-3.3 ppm and absence of olefinic hydrogens. The isomeric epoxides had different R f on TLC, however when separation was attempted by flash column chromatography an intramolecular attack of the C-19 oxygen occurred, with cleavage of the epoxides and concomitant de-O-silylation (probably catalyzed by the adsorbent).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation